2015
DOI: 10.1016/j.vetpar.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A molecular and parasitological survey of Hepatozoon canis in domestic dogs in Turkey

Abstract: In this study, asymptomatic dogs in nine provinces of Turkey were surveyed to investigate the prevalence and intensity of Hepatozoon canis infection. DNA obtained from blood samples collected from 694 domestic dogs (243 stray, 288 shelter, and 163 pets) of both genders and varying ages were evaluated by polymerase chain reaction (PCR). In addition, 285 thin blood smears prepared from these blood samples were also evaluated for microscopic examination. Direct microscopy revealed Hepatozoon gamonts in the periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 13 publications
6
38
1
Order By: Relevance
“…Moreover, the molecular method of identification is much more sensitive than microscopy. In addition, Aktas et al [29] found a 4% positive rate in dogs in Ankara, which is much lower than our rate (49.5%). We believe that this is due to the limited number of samples in their study.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the molecular method of identification is much more sensitive than microscopy. In addition, Aktas et al [29] found a 4% positive rate in dogs in Ankara, which is much lower than our rate (49.5%). We believe that this is due to the limited number of samples in their study.…”
Section: Discussioncontrasting
confidence: 90%
“…In a study including a total of 694 dogs from Sakarya, Kocaeli, Mersin, Giresun, İzmir, Elazığ, Erzurum, Ankara and Nevşehir, 3 (1.05%) of the 285 dogs examined were determined to be positive by microscopy and 155 (22.3%) of the 694 dogs were positive for H. canis by PCR. From Ankara, 49 dogs were tested and 2 dogs (4%) were H. canis-positive [29] . In Erzurum Province, 43 (32.3%) of 133 asymptomatic dogs were positive for Hepatozoon spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first clinical case of H. canis infection in a dog was reported by Voyvoda et al (18). Several epidemiological surveys have revealed a high prevalence of H. canis in dogs in Turkey (10)(11)(12)(13). The studies indicated that the prevalence of H. canis infection in dogs varies as 22.3-54.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, although hepatozoonosis is widespread in dogs (10)(11)(12)(13), feline hepatozoonosis has not yet been documented. This case is the first report of molecular identification of Hepatozoon spp.…”
Section: Introductionmentioning
confidence: 99%